Distribution of ilmenite minerals in placer deposits along the middle coast of Southern Brazil using spaceborne and ground-based remote sensing - Gabriel Prates Hallal; Carla Cristine Porcher; Bijeesh Kozhikkodan Veettil; Jean Marcel de Almeida Espinoza; Silvia Beatriz Alves Rolim (PLoS ONE, 2025)
Titanium oxide is of fundamental strategic importance in the global market as it is used as a raw material by several industries, such as medical prostheses, paints, pigments, and, more recently, electronic chips. The main source of titanium oxide is ilmenite, a mineral deposited in many coastal areas of the world, including the state of Rio Grande do Sul in Southern Brazil in its central coastal plain, under specific morphodynamic conditions. Some geological targets, such as mineral oxides, show distinct thermal spectral features. The present study evaluated the surface concentration of ilmenite in Southern Brazil using thermal spectroscopy (μFT-IR). The emissivity spectral signatures of pure ilmenite between 8 and 14 μm were determined and some indicative features were identified. The obtained emissivity spectrum has been employed as a reference for the Spectral Angle Mapper (SAM) and Linear Spectral Unmixing (LSU) image classification algorithms. An image from the Advanced Spaceborne Thermal Emission Radiometer (ASTER) sensor (AST_05 emissivity product) was used to recognize the occurrence and assess the richness of the ilmenite. The outcomes of the present study indicated pixels with ilmenite concentration between 0 and 29.6%, with the highest concentration occurring under the transgressive dune field. In contrast, a lower concentration is found in the backshore. To obtain the degree of purity of the ilmenite, a quantitative microanalysis of the samples was conducted in a scanning electron microscope (SEM), and the results indicated that 80% of the minerals were ilmenite. Qualitative microanalysis showed that ilmenite is in the primary alteration phase, with a low degree of weathering and a lower concentration of impurities. Integrated techniques for analyzing multispectral and hyperspectral data in the thermal infrared were able to identify and map minerals rich in titanium oxide (ilmenite) quickly, effectively, at low cost, and non-destructively.